PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT TORINDO INTERNUSA BATAM - Jurnal Ilmiah Manajemen UPB (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2017)
This study aims to see the impact of competence and motivation on employee performance. This research was conducted at PT Torindo Internusa Batam. The sample in this research is employees of PT Torindo Internusa Batam. From the results of research, it is known that, competence has no significant effect on employee performance. Motivation has a significant effect on employee performance. The test results simultaneously state that competence and motivation simultaneously have a significant effect on employee performance. R square value in this research is 29,5%, it means, competence and motivation able to explain employee performance equal to 29,5%, while the rest 70,5% influenced by other factor not examined in this research.